Perlindungan Hukum Pemegang Saham Minoritas dan Pertanggungjawaban Notaris dalam RUPS PT Tertutup - Susantijo, Susi; Pangesti, Shinta; Halim, Robbyson (Notary Journal, 2021)
In practice, there often occurrs defective procedure when holding a Private Limited Company’s (PLC’s) General Meeting of Shareholders (GMS), which later stated in Deed of the Meeting Resolutions by a Notary. Regarding the defective procedure in GMS, shareholders will surely suffer losses because their rights are violated, especially minority shareholders. Two problems that arise and examined in this study are: How is the legal protection for minority shareholders in a PLC’s GMS? and How is the responsibility of the Notary for making Deed of the Meeting Resolutions from an Extraordinary GMS containing the defective procedures in a PLC? This research is normative legal research. Based on the research conducted, it can be concluded that legal protection for minority shareholders in PLC’s GMS, has been quite well regulated in Laws of the Republic of Indonesia number 40 of 2007 concerning Limited Liability Company. On the other hand, the responsibility of the Notary for making Deed of the Meeting Resolutions from an Extraordinary GMS containing the defective procedures in an LLC is a liability limited to formal truth or formal requirements. Regarding the material truth, it is not the responsibility of the notary but is the responsibility of the legal subject who performed the legal action. Notary in carrying out his position also requires having thoroughness and carefulness in doing any legal action, including making Deed of the Meeting Resolutions.Bahasa Indonesia Abstrak: Dalam praktek, sering sekali terjadi penyelenggaraan RUPS PT Tertutup yang mengandung cacat prosedur, yang kemudian dituangkan dalam Akta Pernyataan Keputusan Rapat oleh Notaris. Terhadap adanya penyelenggaraan RUPS yang mengandung cacat prosedur, para pemegang saham pasti akan mengalami kerugian karena hak-hak mereka dilanggar, khususnya para pemegang saham minoritas. Dua rumusan masalah yang timbul dan diteliti dalam penelitian ini adalah: Bagaimana perlindungan hukum bagi pemegang saham minoritas dalam RUPS PT Tertutup? serta Bagaimana pertanggungjawaban Notaris atas pembuatan Akta Pernyataan Keputusan Rapat dari penyelenggaraan RUPS Luar Biasa yang mengandung cacat prosedur pada PT Tertutup? Penelitian ini adalah penelitian hukum normatif. Berdasarkan penelitian yang telah dilakukan, diperoleh kesimpulan bahwa perlindungan hukum bagi pemegang saham minoritas sehubungan dengan penyelenggaraan RUPS dalam PT Tertutup sudah cukup baik diatur dalam Undang-Undang Republik Indonesia Nomor 40 Tahun 2007 Tentang Perseroan Terbatas (UU PT). Di samping itu, pertanggungjawaban Notaris atas pembuatan Akta Pernyataan Keputusan Rapat dari penyelenggaraan RUPS Luar Biasa yang mengandung cacat prosedur pada PT Tertutup merupakan pertanggungjawaban sebatas pada syarat formal atau kelengkapan formal. Kebenaran materiil bukan tanggung jawab notaris, melainkan masing-masing subjek hukum yang melakukan. Notaris dalam menjalankan jabatannya juga dituntut memiliki ketelitian dan kehati-hatian dalam melakukan setiap perbuatan hukum, termasuk pembuatan Akta Pernyataan Keputusan Rapat.